Dyeing of Sponge Gourd by Different Methods - YILMAZ, BURCU (TAYLOR & FRANCIS INC, 2021)
Sponge gourd is one of the natural fibers, and its products are biodegradable and sustainable. Modifying the surface of fibers with ultrasonic energy can be improving their dyeability, opening up fibers structure and the mass transfer from one medium to another. The aim of this work is to investigate the possibilities of sponge gourd dyeing by reactive dyes with conventional methods and under the ultrasonic power. The color yields, penetration behavior and fastness properties of dyed fibers by different methods were compared to each other. Using ultrasonic energy was increased dye uptake results by 16% than the conventional method (approx. 80% to 93%). The fastness results in washing and dry/wet rubbing were up to 4 gray scale level. The ultrasonic power seems promising since it enhances color yields and reduces process time.
Keywords: Natural fibers; sponge gourd; ultrasound; reactive dyes; LUFFA-CYLINDRICA; FIBERS; ABSORPTION